IMPLEMENTASI LOGIKA FUZZY DALAM OPTIMASI JUMLAH PENGADAAN BARANG MENGGUNAKAN METODE TSUKAMOTO (STUDI KASUS : TOKO KAIN MY TEXT) - Mutammimul Ula (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2014)
Optimization of the amount of procurement carried out by using three variables, namely sales, inventory and procurement. Variable sales consists of two fuzzy sets, namely: down and up, variable inventory consists of two fuzzy sets, namely: a little and a lot, while procurement is made up of two variable fuzzy set, which decreases and increases. By combining all these fuzzy sets, obtained four fuzzy rules, which is then used in each inference. In the inference stage, look for the antecedent membership value (?) and the optimization of the estimated procurement value (z) of each rule. Optimization of procurement of goods (z) sought by an average defuzzification method centralized. Analysis using the Tsukamoto method produces the optimum conditions of procurement reaches 38 cloth / bales, this approach calculations generated by Shop My Text without using methods Tsukamoto, ie 35 cloth / bales. Analysis using the Tsukamoto method shows the real condition that must be carried out by the seller of goods in store My Text in the procurement process so that more targeted.